1990
DOI: 10.1096/fasebj.4.11.2199283
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of spontaneous diabetic kidney disease

Abstract: Kidney disease, characterized by proteinuria and glomerular lesions, is a common complication of spontaneous diabetes mellitus in many animal species. It occurs in animals with hypoinsulinemia, hyperinsulinemia, or impaired glucose tolerance. The renal functional and structural abnormalities in spontaneously diabetic animals resemble human diabetic nephropathy in many respects. Mesangial expansion and glomerular basement membrane thickening, two structural hallmarks of diabetic glomerulopathy in humans, are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 0 publications
0
69
0
4
Order By: Relevance
“…Accordingly, reduction of AS density in GBMs is widely regarded as contributory to diabetic proteinuria. However, since only modest levels of urine protein have been reported for moderately hyperglycemic BB rats (Cohen et al, 1987;Velasquez et al, 1990;Zamlauski-Tucker et al, 1992;Feld et al, 1995), it seems possible that maintenance of normal complements of AS as shown in the current investigation may be related functionally to known relatively low levels of proteinuria in diabetic BB rats.…”
Section: Electron Microscopic Studiesmentioning
confidence: 65%
See 1 more Smart Citation
“…Accordingly, reduction of AS density in GBMs is widely regarded as contributory to diabetic proteinuria. However, since only modest levels of urine protein have been reported for moderately hyperglycemic BB rats (Cohen et al, 1987;Velasquez et al, 1990;Zamlauski-Tucker et al, 1992;Feld et al, 1995), it seems possible that maintenance of normal complements of AS as shown in the current investigation may be related functionally to known relatively low levels of proteinuria in diabetic BB rats.…”
Section: Electron Microscopic Studiesmentioning
confidence: 65%
“…increased MM is considered a hallmark for diabetes in human and some animal models (Velasquez et al, 1990;Viberti et al, 1994). However, mesangial expansion in moderately hyperglycemic BB rats generally is reportedly unremarkable or absent (Brown et al, 1983;Cohen et al, 1987).…”
Section: Light Microscopic Studiesmentioning
confidence: 99%
“…Most experimental models of diabetic nephropathy are different from human pathological lesions (10,30). On the other hand, the iNOSTg mice showed remarkably advanced glomerular lesions that resemble human diabetic glomerulosclerosis.…”
Section: Quantitation Of the Expression Ratio Of Hsp47/gapdh Mrna Andmentioning
confidence: 95%
“…Spiny mouse (Acomys calirinus) is another small rodent living in semiarid areas of eastern Mediterranean. They gain weight and exhibit marked impaired pancreatic beta cell when they are placed in captivity on high energy rodent lab chow [135]. Ctenomis talarum (Tuco-tuco) is another feral species which exhibit similar characteristic features of sand rat and spiny mice when fed on high energy rodent diet [136].…”
Section: Spontaneous Animal Models Of Lipoprotein Disordersmentioning
confidence: 99%